Long-Term Study of the Relationship between Precipitation and Aquatic Vegetation Succession in East Taihu Lake, China - Yehui Zhang; Na Yang; Jiawei Xu; Yixing Yin (Scientifica)
Based on long-term rainfall measurements (1956–2012), water level records (1956–2006), and aquatic plants field survey data (1960–2014), the relationship between precipitation and aquatic vegetation succession in east Taihu Lake, China, is studied. Neither abrupt changes nor any trends were found in the annual rainfall series in Taihu Lake during the studied period (1956–2012). However, for seasonal variations, statistically significant decreases are found in spring and autumn, while the rainfall in winter exhibits statistically significant increase. No significant trend was obtained in summer. A “dry” period was detected in our studied period (1963/1964~1978/1979). Total annual rainfall was significantly positively correlated to the number of rain-days (r=0.59) and the water level (r=0.84). Our results indicate that the variations of rainfall and water level may have an impact on the aquatic plants in Taihu Lake. The dry period may be not suitable for the growth of the aquatic plants. All aquatic plants in Taihu Lake were dramatically reduced in the dry period, especially for submerged macrophytes and floating-leaf macrophytes. Our results may be helpful for the aquatic restoration in the future.